Design of a compact printed band-notched antenna for ultrawideband communications - Mohd Sobli, Nuurul Hudaa; Abdel-Raouf, Hany Essam Eldin (EMW Publishing, 2008)
A compact printed ultra-wideband (UWB) antenna with band-notched characteristic is presented. The antenna is designed to cover the Federal Communications Commission (FCC) bandwidth for UWB applications (3.1--10.6 GHz) with band-notched at frequency band (5.15--5.825 GHz). The proposed antenna is fed by microstrip line, and it consists of square radiating patch on the top layer with a slotted-parasitic patch on the bottom layer of the antenna. The slotted-parasitic patch acts as a notch filtering element to reject the frequency band (5.15--5.825 GHz) which is used by IEEE 802.11a and HIPERLAN/2. Moreover, the pulse distortions of different input pulses are investigated based on S21 parameters for two cases; face to face and side by side orientations. There is a small acceptable influence on the matching between the input and the output pulses and it is found that the pulse distortion is low. Therefore, the proposed antenna is a good candidate for UWB applications.